A proposed roadmap for the control of infections in wildlife using Chlamydia vaccine development in koalas Phascolarctos cinereus as a template. Issue 1 (3rd February 2020) - Waugh, Courtney A.; Timms, Peter
Abstract : Vaccination strategies provide a crucial tool for managements of disease risks in wildlife, but have been utilized mostly for domestic species. However, a significant body of work has now been published describing the successful development of an anti‐chlamydial vaccine for the koala Phascolarctos cinereus, Goldfuss, 1817. As such, vaccinations against these infections in the koala, can provide important insights into the use of vaccines for wildlife. Chlamydia infections in the koala have been intensively studied for over 30 years. Infections cause severe disease states, such as kerato‐conjunctivitis (blindness) and reproductive tract disease (infertility), and/or mortality; and are contributing significantly to population declines. We aim to use the plethora of data available from koala chlamydial studies as a template to propose a roadmap for the development of vaccines for other wildlife species, especially in this era of antibiotic resistance. As such we have outlined the important steps that have led to significant milestones resulting in the successful development of a vaccine against an infectious disease in a non‐domestic species. We hope to thus provide, not only a timely review on Chlamydia vaccines in koalas, but also an important conservation and management roadmap to help guide future researchers that are considering the development of a vaccine for a wild species.